Implementation of the Public Green Open Space Provision Policy in Supporting Ecological Functions in Padang City - Adrianus Tafoguna Hia; Intan Slipilia (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Public green open space (Ruang Terbuka Hijau; RTH) is essential for maintaining urban ecological functions, particularly rainwater infiltration and shading. Although Padang City has met the minimum RTH provision requirement mandated by Law Number 26 of 2007, compliance with the required area does not necessarily ensure optimal ecological performance. This study aimed to analyze the implementation of the RTH provision policy in supporting ecological functions in Padang City and to identify the constraints affecting its implementation. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation and analyzed through data reduction, data display, and conclusion drawing. The analysis was guided by George C. Edward III’s policy implementation framework, encompassing communication, resources, disposition, and bureaucratic structure. The findings indicate that the Environmental Agency of Padang City has implemented the policy through park maintenance, rehabilitation, and management activities. Internal communication among implementers has functioned effectively, but public dissemination of information concerning the ecological functions of RTH remains limited. Implementation has also been constrained by insufficient human resources, limited budget allocation, inadequate technical competencies, and a lack of supporting facilities, despite strong implementer commitment, clearly defined responsibilities, and established standard operating procedures. These constraints have weakened the rainwater infiltration function, as reflected in clogged drainage systems, the absence of infiltration wells and retention ponds in all parks, and the prevalence of paved surfaces in several locations. By contrast, the shading function has performed relatively well, although vegetation in some parks has not yet reached optimal maturity. The study concludes that RTH policy implementation should be evaluated not only according to compliance with statutory area requirements but also according to the effectiveness of urban parks in performing their ecological functions. These findings contribute to urban environmental policy implementation by emphasizing the need to strengthen institutional resources, expand public environmental education, and improve sustainable park management in Padang City.